Severity of Cardiovascular Autonomic Neuropathy in Type 2 Diabetes Mellitus Patients : Correlation with Duration of Diabetes (International Journal of Physiology, 2019)
IntroductionCardiovascular Autonomic Neuropathy (CAN) is one of the most overlooked complications of DM and is clinically important because of its life threatening consequences. CAN results from damage to the autonomic nerve fibers that innervate the heart and blood vessels.Aims and ObjectivesThe aim of the present study is to assess the correlation between severity of cardiovascular autonomic functions in type 2 DM and duration of diabetes.MethodThe study included 30 cases of type 2 diabetes mellitus without diabetic retinopathy and 30 cases of type 2 diabetes mellitus with non proliferative diabetic retinopathy (NPDR). 60 non diabetic healthy volunteers matched for age and gender were included in the study to serve as control. The study group was classified into 3 groups according to duration of diabetes. All the subjects performed five different autonomic function tests as given by Ewing's and Clarke. The score value was obtained from various tests and a scoring system was applied as recommended by Bellavere F et al (1983).4 The results obtained were analysed statistically by one-way ANOVA and intergroup comparisons were made using post hoc Tukey multiple comparison test.ResultsThe observations suggest that cardiac autonomic function declines in type 2 diabetics and CAN is more in diabetic patients with associated retinopathy The observations revealed that number of patients with autonomic dysfunction was more when duration of DM was long (>7 years) (83.3% in group 1 and 81.2% in group 2). The number of patients with CAN increased with duration of DM. Correlation between disease duration and cardiovascular autonomic score indicates significant positive correlation (r=0.5920).ConclusionThe cardiac autonomic functions were found to be altered significantly in diabetics. Diabetic patients with longer duration of diabetes showed more severe dysfunction of cardiovascular functions. Hence, Evaluation of cardiovascular reflexes should be included as a routine in the work-up of patients of Type 2 diabetes mellitus.